DESIGNING PRESS MACHINE CANNED SOFTDRINK TO REDUCE VOLUME WASTE OF CANNED SOFTDRINK: DESIGNING PRESS MACHINE CANNED SOFTDRINK TO REDUCE VOLUME WASTE OF CANNED SOFTDRINK - Mukhtar, Nushron Ali (UNIPA PRESS, 2018)
Many processes in the industry originally done by humans, are now being replaced by machines that are driven automatically by simply giving commands / programs or just simple / semi-automatic buttons. This is intended for human energy efficiency and the effectiveness of completion time, due to the rapid progress of human resources (Human Resources) so that it is no longer possible to do the work manually with great energy.This Final Project aims to plan, manufacture, and test semi-automatic press machines for the purpose of automation of engine press. Methods in the design of this machine is the study of observation. From the design is done, generated a semi-automatic press machine, with the following specifications: Capacity of compressive strength with the power of pressing 150 kg. The electric motor used has a power of 0.5 PK and 1400 rpm rotation. Total cost for the manufacture of 1 unit of this machine is Rp 1.714.000, -.